14-years Old Ian Thorpe's Full Stroke During His 400 m Bronze Medal Race at the 1997 Pan Pacific Championships, Fukuoka, Japan - Rushall, B. S.
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for 14-years old Ian Thorpe's full stroke during his 400 m bronze medal race at the 1997 Pan Pacific Championships, Fukuoka, Japan. Ian Thorpe's stroke demonstrates a four-beat kick for each arm pull. Because of the length of time that an arm is underwater, time is available to perform that number of kicks. A kick is performed to counter-balance each arm entry and exit. Since a large part of both arm propulsive phases is executed with the other arm extended forward, a considerable part of the latter half of force generation is conducted mainly with internal rotator muscles of the shoulder, lower arm rotators, and elbow extensors. This is occasioned by relatively flat shoulders. Time will tell if this specific localization of effort will prove to be troublesome. Several facets of this stroke are worthy of emulation or adaptation. A major strength of Ian Thorpe's stroke is the length of time spent generating direct forces. His left arm movement is brilliant, his streamlining superb, and his potential unknown. With maturation, this individual should re-write the record books.